Universal Amplification-Free RNA Detection by Integrating CRISPR-Cas10 with Aptameric Graphene Field-Effect Transistor - Mingyuan Sun; Zhenxiao Yu; Shuai Wang; Jiaoyan Qiu; Yuzhen Huang; Xiaoshuang Chen; Yunhong Zhang; Chao Wang; Xue Zhang; Yanbo Liang; Hong Liu; Qunxin She; et al. (Nano-Micro Letters)
Highlights A collaborative biosensing system is developed for amplification-free RNA/miRNA detection by integrating Type III CRISPR-Cas10 system with a graphene field-effect transistor (GFET). Continuous cleavage of ssDNA by the mutant CRISPR-Cas10 effector complexes and high charge density of hairpin DNA reporters on the GFET channel enable the detection limit to reach the level of aM. A universal sensing detection platform is established to directly detect the medium-length RNAs and miRNAs in clinical samples with the recognition capability of single nucleic acid.